Implementation of Environmental Awareness in the Legon Wetan Mangrove Area, Legon Kulon District, Subang Regency - Afriza, Lia; Larasati, Ajeng Ramadhita; Salsabila, Siti Reisa; Fitriyani, Yuni (Ann Publisher, 2025)
Background. The mangrove ecosystem in Legon plays a vital role in maintaining the balance of the coastal ecosystem while preserving economic potential through the development of ecotourism and products based on local resources. However, challenges in the form of environmental degradation and low community participation are the main obstacles in the utilization of this potential. Purpose. Increase awareness, capacity, and the active role of local communities in mangrove conservation through a community-based conservation (CBC) approach. The methods used include area mapping, environmental socialization and education, technical training on conservation and processing of mangrove-based products, coastal clean-up and replanting actions, and the formation of local driving communities. Result. The results of the activity included increased community participation, the formation of the